Platform Pemesanan dan Pelacakan Pengiriman Beton Siap Pakai Berbasis Web dan Mobile dengan Pendekatan SDLC dan TAM - M Rifqi Al Amin Sp; Joko Aryanto (Bulletin of Computer Science Research, 2025)
This study aims to develop a web and mobile-based platform for ordering and delivering ready-mix concrete as a solution to delays and data errors frequently found in manual processes. The system is designed to simplify the ordering process for customers while enabling suppliers to manage deliveries and production schedules in real-time. The research applies the System Development Life Cycle (SDLC) framework and refers to the Technology Acceptance Model (TAM) to ensure that the system is user-friendly and meets user needs. Data were collected through business process observation and system requirements analysis, and the platform was implemented using modern web and mobile technologies. The results show that the developed system increases ordering efficiency by up to 40% and reduces delivery errors by 25% compared to manual methods. Additionally, the platform offers an interactive dashboard that enables both customers and suppliers to monitor order status accurately. Based on these findings, it can be concluded that the developed platform effectively supports the digital transformation of business processes in the ready-mix concrete industry, enhancing the service quality of construction companies.